2022
DOI: 10.2147/idr.s350048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Prevalence and the Risk Factors of Gram-Negative Multi-Drug Resistant Bacteria in Eastern Saudi Arabia

Abstract: Purpose Multidrug-resistant organisms (MDROs) among Gram-negative bacteria (GNB) are a major public health concern worldwide, which can even lead to death. This study was conducted to determine the prevalence of MDROs among isolated GNB in the Security Forces Hospital Dammam (SFHD) and identify its associated risk factors. Materials and Methods A cross-sectional study was performed on the most commonly isolated GNB in SFHD, Acinetobacter spp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 15 publications
6
30
1
Order By: Relevance
“…In addition, patients submitted to mechanical ventilation (P= 0.005) were at a greater risk (Table 4). These findings align with the results described by Al Hamdan et al 17 . Undergoing surgical intervention was another independent predictor for MDR Gram-negative ESKAPE infections, which corroborates other researchers 30 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, patients submitted to mechanical ventilation (P= 0.005) were at a greater risk (Table 4). These findings align with the results described by Al Hamdan et al 17 . Undergoing surgical intervention was another independent predictor for MDR Gram-negative ESKAPE infections, which corroborates other researchers 30 .…”
Section: Discussionsupporting
confidence: 93%
“…In our univariate analysis, increased age beyond 60 years was significantly associated with acquiring MDR Gram-negative ESKAPE infections (P= 0.009), similar to another study from Saudi Arabia 17 . In elderly patients, jeopardized immune system sets them at a higher risk for hospitalization and having infections with virulent strains, including antibiotic-resistant bugs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2 Moreover, the intrinsic resistance is highly important as it along with other resistance mechanism may result in poor clinical outcome. 4 , 5 Further, this study reported 16.7% (1 out of 6 strains) resistance in Streptococcus pneumoniae to penicillin. However, CLSI guidelines have not recommended to report penicillin resistant S. pneumoniae strains on the basis of disk diffusion method(s).…”
Section: Dear Editorsupporting
confidence: 51%
“…2 Moreover, the intrinsic resistance is highly important as it along with other resistance mechanism may result in poor clinical outcome. 4 , 5 …”
Section: Dear Editormentioning
confidence: 99%